Enhancing Digital Literacy: An Analysis of Islamic Primary School Prospective Teachers' Competency in Navigating the Digital Era - Maya Agustina; Rina Rahmi; Aidil Saputra (Jurnal Ilmiah Sekolah Dasar, 2024)
The big data era demands an enhancement in human resource quality, particularly in mastering digital skills, including digital literacy. As part of the younger generation, university students must possess adequate digital literacy to support their academic and professional activities. This study aims to analyze the digital literacy proficiency of students in the Islamic Primary School Teacher Education (PGMI) program using a quantitative approach through a survey method. The study population consisted of 801 students, with a sample of 209 students selected using the stratified random sampling technique. The research instrument was a questionnaire with a Likert scale covering indicators of Digital Skills, Digital Culture, Digital Safety, and Digital Ethics. The findings indicate that the digital literacy proficiency of PGMI students falls within the "Good" category, with an overall percentage of 77%. Specifically, Digital Skills achieved a score of 85% ("Very Good"), Digital Culture 79.5% ("Good"), Digital Safety 75.2% ("Good"), and Digital Ethics 68.8% ("Good"). The aspect of Digital Ethics involves responsible social media use, such as avoiding the spread of misinformation or hoaxes. The study concludes that PGMI students possess a generally good level of digital literacy; however, further reinforcement is needed, particularly in the area of digital ethics, to better prepare them for the challenges of the digital era.